Investigating the Gut Microbiota Profile in Prehypertensive Individuals Exhibiting Phlegm-Dampness Constitution - Yu, Ning; Yang, Yaotang; Wang, Guangyun; Wang, Yanhong; Feng, Mei; Yang, Peilin; Liu, Shuang; Wang, Rui-rui; Zhang, Lei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPrehypertension is the preclinical stage of hypertension, which is more likely to develop into hypertension than normal blood pressure. Although the body may experience pathological changes at this stage, there are often no symptoms. Chinese medicine constitution theory is widely used to assess an individual’s health and disease status, which provides a new method for disease prevention. The phlegm-dampness constitution (PDC) is the main constitution in prehypertension. Dysbiosis of the intestinal flora is considered to be related to the development of hypertension. However, the characteristics of the intestinal flora in prehypertensive populations with PDCs are still unknown.Methods16S rRNA gene sequencing of fecal samples was performed in this study, which included 30 prehypertensive subjects with PDCs, 30 nonphlegm-dampness constitution (NPDC) prehypertensive individuals with balanced constitution, and 30 ideal blood pressure subjects with balanced constitution (BC). On the basis of the composition of the intestinal flora, a random forest classifier was constructed to screen the specific bacteria of the prehypertensive PDC population, and the diagnostic efficiency was determined by the area under the curve (AUC).ResultsAt the phylum level, the abundance of Bacteroidetes decreased in the PDC group compared with the NPDC group. Bacteroides was the most important genus at the genus level. Compared with those in the NPDC or BC group, the relative abundances of o_RF39, f_Porphyromonadaceae, f_Christensenellaceae, g_parabacteroides, and g_nitrobacteria in the PDC group were significantly greater. The random forest analysis results revealed that Alistipes, Butyricimonas, Odoribacter, Parabacteroides, and Corynebacterium are bacterial genera that significantly differ between the PDC and NPDC groups and greatly contribute to group differentiation. Receiver operating characteristic (ROC) analysis revealed that the AUC range of differential bacteria and its combined diagnostic model ranged from 0.653 (95% CI: 0.511–0.794) to 0.706 (95% CI: 0.573–0.838), suggesting that it is a potential risk marker for phlegm-dampness constitution with prehypertension.ConclusionsOur study indicates that PDC individuals with prehypertension can be distinguished from NPDC individuals according to their gut microbiome characteristics. Prevention and treatment measures based on these biomarkers may be beneficial in opening new ideas and directions for identifying more aggressive and effective interventions for prehypertensive populations.